Інформаційна система для визначення стану пульпи зуба - Самохін, Ю. В.; Соколов, Д. Ю. (ХНУРЕ, 2019)
The purpose of this work is to develop a device that takes into account not only the excitability of nerve fibers, but also the functional properties of pulp tissue. For this purpose, the authors propose to take into account, in the indications of the device, the electrical resistance of the tissues of the tooth, including the pulp. The developed device allows in real time to determine the state of the pulp of the tooth to be studied and provides the opportunity to quickly make a decision on the choice of adequate treatment. This device can facilitate the work for dentists and speed up the treatment process